Pelaksanaan Jaminan Fidusia Pada Pembiayaan Murabahah Di Bank BNI Syariah Kantor Cabang Probolinggo - Rizal, Sofian Syaiful; Insiyah, Insiyah (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2021)
The practice of implementing fiduciary guarantees on murabahah financing at Bank BNI Syariah provides legal certainty for Islamic banks as creditors. Given that many Islamic banks have implemented fiduciary guarantees as additional collateral for murabahah financing, the research method used is descriptive qualitative research. After the research process has been carried out, In practice, the fiduciary security must first be registered at the fiduciary security office, which Bank BNI Syariah represents to a notary. If there is a debtor default at Bank BNI Syariah, it will be resolved by sharia principles, namely by providing guidance and visits to the debtor. If there is still no good intention from the debtor to carry out their obligations then Bank BNI Syariah will execute objects bound by fiduciary by legal process. The conclusion is that the implementation of the fiduciary guarantee policy at the Bank BNI Syariah Probolinggo Branch Office must use a fiduciary binding as long as the murabahah object is a moving object.